2008
DOI: 10.1111/j.1537-2995.2008.01719.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of hemoglobin mass after blood donation

Abstract: The results of this study confirm the minimal, recommended donation intervals (56 days for men) as adequate when, for the first time, judged upon by tHb as a direct marker of hematologic recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 24 publications
(37 reference statements)
7
68
0
Order By: Relevance
“…98 The loss of Hb mass of approximately 75 g (measured by CO rebreathing) after donation of 550 mL blood has been shown to be recovered after a mean of 36 days. 99 After the retransfusion of one RBC unit Hb mass acutely increased by 51 g, showing a continuous decrease from week 2 until week 8, albeit Hb mass was still elevated compared with pre-reinfusion values. 100 Based on the results of a retrospective longitudinal blinded study, the same group of investigators has reported that the use of an adaptive model incorporating hematologic measures ([Hb], reticulocyte percentage, OFF-score) allows for detection of autologous blood transfusion.…”
Section: Rbc Parameters Associated With Autologous Retransfusionmentioning
confidence: 89%
“…98 The loss of Hb mass of approximately 75 g (measured by CO rebreathing) after donation of 550 mL blood has been shown to be recovered after a mean of 36 days. 99 After the retransfusion of one RBC unit Hb mass acutely increased by 51 g, showing a continuous decrease from week 2 until week 8, albeit Hb mass was still elevated compared with pre-reinfusion values. 100 Based on the results of a retrospective longitudinal blinded study, the same group of investigators has reported that the use of an adaptive model incorporating hematologic measures ([Hb], reticulocyte percentage, OFF-score) allows for detection of autologous blood transfusion.…”
Section: Rbc Parameters Associated With Autologous Retransfusionmentioning
confidence: 89%
“…Indeed, several studies show that ferritin levels drop by about 50% after blood donation and that this effect worsens with frequent donation [30,31]. It has also been observed that a 4-month interval between donations is not sufficient to restore ferritin levels [31,32]. Thus, it is unlikely that the ferritin levels of the volunteers would have returned to baseline by the time the transfusion phase started (5 weeks after the blood donation).…”
Section: Research Articlementioning
confidence: 99%
“…The body will restore total blood volume within 3 days after donation, initially through plasma expansion, which occurs within the first week after donation (17). Plasma recovery occurs much faster than restoration of red cell volume after blood loss (17). The initial plasma volume expansion will result in an isovolumic anemia whereby RBC concentration is diluted.…”
Section: Introductionmentioning
confidence: 98%
“…Decreased blood volume accompanied by decreased red cell volume may result from surgery, through donation, or because of injury (18). The body will restore total blood volume within 3 days after donation, initially through plasma expansion, which occurs within the first week after donation (17). Plasma recovery occurs much faster than restoration of red cell volume after blood loss (17).…”
Section: Introductionmentioning
confidence: 99%